1998
DOI: 10.1177/1087724x9800300203
|View full text |Cite
|
Sign up to set email alerts
|

Size and Cost Efficiency in the Production of Local Road Services

Abstract: The authors analyze 925 town highway departments in New York to determine potential economies from consolidation and the degree of cost efficiency. Only 15% of departments would reduce costs by merging, resulting in an average 13% reduction in expenditures. In addition, all of the towns are cost inefficient by an average 17%. Size economies are estimated using a log quadratic stochastic frontier regression model. The estimated cost curve is a textbook U shape with a mean cost elasticity of 0.97, indicating tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
1
Order By: Relevance
“…They also found that input proportions were not cost minimizing, but did not quantify the resulting allocative ineffi ciency. And the estimated mean u = 0.31 reported in this paper for small water systems is notably higher than the u = 0.16 reported for local highway departments in New York by Helfrich and Vitaliano (1998), who also employed a stochastic frontier cost function.…”
Section: Estimated Inefficiencycontrasting
confidence: 73%
“…They also found that input proportions were not cost minimizing, but did not quantify the resulting allocative ineffi ciency. And the estimated mean u = 0.31 reported in this paper for small water systems is notably higher than the u = 0.16 reported for local highway departments in New York by Helfrich and Vitaliano (1998), who also employed a stochastic frontier cost function.…”
Section: Estimated Inefficiencycontrasting
confidence: 73%